Perbandingan Arus Puncak Ekspirasi (APE) antara Perokok dan Bukan Perokok pada Mahasiswa Fakultas Hukum Universitas Mataram - Agus Putradana; Eva Marvia; Dina Fithriana; Zatul Yatin Masri (LPPM STIKES Mataram, 2023)
Introduction: Cigarettes contain various kinds of toxic chemicals that are dangerous to the health of conventional smokers, electric smokers and non-smokers. One of the contents of cigarettes, namely formaldehyde, when exposed to the human body can cause oxidative stress as well as DNA damage in the bone marrow, both of which will disrupt the respiratory and circulatory systems, such as Oxygen Saturation and Peak Expiratory Flow (henceforth PEF. Purpuse: Therefore, the purpose of this study was to determine the ratio of PEF between smoking and non-smoking students of the Faculty of Law, University of Mataram. Methods: This research was designed as analytic observational with cross sectional. The population of this study was 518 students. By using the accidental sampling technique, the sample was obtained as many as 72 respondents divided into categories of conventional smokers (24), electric smokers (24), and non-smokers (24). Measurement of PEF was conducted by using a mini Wright peak flow meter and data collection was conducted by using a questionnaire. Data were analyzed by independent t test and Mann-Whitney test. Result: Of the 72 respondents consisting of 3 categories, the majority were aged between 20-24 years with height 165-177 cm, the majority of mild smokers were in the electric smoker category, while conventional smokers were 50% mild smokers, 42% moderate smokers and 8% severe smokers. Pneumoblie values in conventional smokers were 50% green zone and 50% yellow zone, electric smokers and non-smokers were in the green zone 100%. The results of the independent t test showed p value: 0.000 <0.05 which means that there was a difference in the PEF value of conventional smokers and electric smokers. Mann-Whitney test analysis obtained p value: 0.000 <0.05, which means that there was a difference in the PEF value of smokers and non-smokers. Suggestions: Recommendations for future researchers to add characteristics of respondents based on the level of severity of smoking habits.